2018
DOI: 10.1142/s2010135x18500303
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structural investigation, dielectric and magnetic properties of Zn2+-doped cobalt ferrite by the sol–gel technique

Abstract: Zinc substituted cobalt ferrite nanoparticles with elemental composition Co[Formula: see text]ZnxFe2O4 ([Formula: see text], 0.2, 0.4, 0.6) were prepared by the sol-gel auto-combustion technique using Co, Fe, Zn nitrate as a precursor where nitrates to citrate was 1:3. The as prepared powder of cobalt zinc ferrite was sintered at 900∘C for 3[Formula: see text]h. Structural, morphological, dielectric and magnetic properties were studied by x-ray diffractometer (XRD), scanning electron microscope (SEM), high pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(12 citation statements)
references
References 32 publications
(24 reference statements)
0
11
1
Order By: Relevance
“…10). These values show significant decrease compared to that obtained from the synthesis of zinc cobalt ferrite by Mohammad Sajjad Hossain et al [16] (HC=726.13 Oe). This reduction is attributed to the movement of Co 2+ ions to the tetrahedral position [3].…”
Section: Magnetic Propertiescontrasting
confidence: 53%
See 1 more Smart Citation
“…10). These values show significant decrease compared to that obtained from the synthesis of zinc cobalt ferrite by Mohammad Sajjad Hossain et al [16] (HC=726.13 Oe). This reduction is attributed to the movement of Co 2+ ions to the tetrahedral position [3].…”
Section: Magnetic Propertiescontrasting
confidence: 53%
“…. In addition, according to Wuhlfarth's theory, anisotropic constant (K) and magnetic moment (nB) for the formula unit are obtained by Equations(3)(4)(5)(6)(7)(8) and(3)(4)(5)(6)(7)(8)(9) [4,16,39]:…”
mentioning
confidence: 99%
“…The resultant material had 70 nm crystallites with a saturation magnetization (Ms) of 86 emu/g. The sol-gel method is extensively used for the synthesis of spinel ferrites [50][51][52][53][54][55]. The process involves the transition of a system from a liquid phase (sol) to a solid phase (gel), through chemical reactions such as hydrolysis and condensation polymerization of the metallic precursors [25].…”
Section: Methods Of Synthesis Of Magnetic Spinel Ferritesmentioning
confidence: 99%
“…11From a closer look at the data, it is observed that έ diminution continuously with increasing frequency. All samples revealed dispersion due to Maxwell-Wagner interfacial polarization [34][35][36][37] The numbers of Fe 2+ ions on B sites, which participate in electron exchange interaction, are responsible for the polarization and maximum in case of cobalt ferrite. As the zinc, content in the mixed Co-Zn ferrites is continuously increased the number of ferrous ions on the B sites which are available for polarization decreases, resulting in a continuous decrement in the dielectric constant.…”
Section: Transport Propertiesmentioning
confidence: 99%